Active Oceanic Detachment Faulting at the Ultraslow Spreading Mohns-Knipovich Ridge Bend: A 12 Month Microseismicity Study - Pilot, Matthias (2022)
At ultraslow spreading ridges magma supply is limited and spreading is often accommodated by tectonic extension, resulting in large offset normal faults. When these initially steep normal faults roll over to lower angles at shallow depths they are called detachment faults. They can expose mantle rocks at the seafloor and act as pathways for hydrothermal fluid circulation. With only a few long-term seismicity studies of active oceanic detachment faults, many of the ongoing deformation processes are still under debate. While earthquakes appear to delineate the detachment surface, seismicity within the footwall of the detachment has been contrarily related to either compressional stresses from bending-related forces or extensional stress due to solid-block rotation. This thesis aims to provide further insights into the seismic characteristics of an active spreading system and the processes related to active oceanic detachment faulting. A microseismicity dataset was recorded during a 12 months Ocean Bottom Seismometer deployment at the Mohns-Knipovich Ridge bend along the ultraslow spreading Arctic Mid Ocean Ridge system. From the whole dataset microearthquakes were extracted and subsequently picked with automatic earthquake detection and phase picking algorithms. For this thesis a sub-catalogue of the strongest 1534 events was extracted. It consisted of events with phase picks on at least seven stations which were manually re-picked. To find the best location procedure, two velocity models and two location algorithms with station corrections derived for each of the procedures were used. From the results of the best location procedure 1215 well-constrained events were selected for further interpretation. The location results reveal a shallowing brittle-ductile transition zone from ∼6-5 km depths towards the Loki’s Castle hydrothermal vent field. This could indicate the presence of a heat source beneath the axial volcanic ridge. An active detachment fault, dipping at ∼70 ◦ towards the SE, shows continuous seismic ...